MENINGKATKAN SIKAP KEMANDIRIAN BELAJAR PESERTA DIDIK MELALUI KEGIATAN EKSTRAKURIKULER DI SDN 5 LIMBOTO - Arten Mobonggi; Ruwiah A. Buhungo; Fradita S. Bonde (RUMAH JURNAL - LP2M IAIN SULTAN AMAI GORONTALO JURUSAN PENDIDIKAN GURU MADRASAH IBTIDAIYAH (PGMI) FAKULTAS ILMU TERBIYAH DAN KEGURUAN, 2021)
This article aims to improve students' learning independence through extracurricular activities at SDN 5 Limboto. The type of research is descriptive qualitative research that uses scientific research as a data source to obtain data from various sources, namely primary data and secondary data, while data collection uses interview, documentation and observation techniques and to check the validity of using triangulation techniques. The results showed that increasing the learning independence of students through extracurricular activities at SDN 5 Limboto was carried out using the right method to instill some independence attitudes.